The Influence Of Financial Literacy On Financial Management Behavior In Indonesian Parahikma Institute Students - Nurul Haeriyah Ridwan; Ryo Sinung Primadanar (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Financial literacy has become an important skill required in everyday life. Due to the instability of the global economy, consumers face financial decisions that have become more complex due to increasing product variety and financial challenges. Therefore, the importance of financial management skills in personal life has increased and more and more research has explored this issue in the last decade. This positive attitude will help them to practice good personal financial management as working adults. The research method used by researchers is a quantitative research method using a quantitative approach. The form of research used is correlation research in the form of causal relationship regression. The research was carried out at the Indonesian Parahikma Institute of Higher Education, specifically the Islamic Education Management Study Program, with a population of 60 students from the Islamic Education management study program. Of the 60 selected students, 60 were used as research samples. The researcher's sampling technique used saturated samples. The data collection tools used were test questions and questionnaire sheets by distributing questionnaires online via Google Form, and then tabulating using the SPSS computer program. Meanwhile, the data analysis technique used in this research starts from testing the instrument by testing the Validity and Reliability of the Questionnaire using the Product Moment and Spearman Brown tests. In accordance with the results of the research that has been conducted, it was found that financial literacy has a significant effect on financial management behavior among Parahikma Indonesia Institute students.